Observed response of stratospheric and mesospheric composition to sudden stratospheric warmings. (15th September 2019) - Denton, M.H.; Kivi, R.; Ulich, T.; Rodger, C.J.; Clilverd, M.A.; Denton, J.S.; Lester, M.
Abstract: In this study we investigate and quantify the statistical changes that occur in the stratosphere and mesosphere during 37 sudden stratospheric warming (SSW) events from 1989 to 2016. We consider changes in the in-situ ozonesonde observations of the stratosphere from four sites in the northern hemisphere (Ny-Ålesund, Sodankylä, Lerwick, and Boulder). These data are supported by Aura/MLS satellite observations of the ozone volumetric mixing ratio above each site, and also ground-based total-column O3 and NO2, and mesospheric wind measurements, measured at the Sodankylä site. Due to the long-time periods under consideration (weeks/months) we evaluate the observations explicitly in relation to the annual mean of each data set. Following the onset of SSWs we observe an increase in temperature above the mean (for sites usually within the polar vortex) that persists for >∼40 days. During this time the stratospheric and mesospheric ozone (volume mixing ratio and partial pressure) increases by ∼20% as observed by both ozonesonde and satellite instrumentation. Ground-based observations from Sodankylä demonstrate the total column NO2 does not change significantly during SSWs, remaining close to the annual mean. The zonal wind direction in the mesosphere at Sodankylä shows a clear reversal close to SSW onset. Our results have broad implications for understanding the statistical variability of atmospheric changes occurring due to SSWs and provides quantification of such changes for comparison with modelling studies. Highlights: Locations inside PV show strong changes due toSSWs. No changes are observed at sites consistently outside the PV. Increase in mean temperature first observed at ∼60 km altitude and then at lower altitudes. Average duration of temperature increase is ∼40 days. Increase in O3 (of ∼20% above the monthly mean) at highest latitude sites. Persists for ∼40 days. Good agreement betweenstatistical ozonesondes and Aura/MLS. Column NO2 unchanged during SSWs. Column O3 decreases prior to SSW and then increases sharply. This increase persists for in excess of 40 days.